2020
DOI: 10.3390/nu12061742
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Lipopolysaccharide-Induced Acute Lung Injury by Hispolon in Mice, Through Regulating the TLR4/PI3K/Akt/mTOR and Keap1/Nrf2/HO-1 Pathways, and Suppressing Oxidative Stress-Mediated ER Stress-Induced Apoptosis and Autophagy

Abstract: The anti-inflammatory effect of hispolon has identified it as one of the most important compounds from Sanghuangporus sanghuang. The research objectives were to study this compound using an animal model by lipopolysaccharide (LPS)-induced acute lung injury. Hispolon treatment reduced the production of the pro-inflammatory mediator NO, TNF-α, IL-1β, and IL-6 induced by LPS challenge in the lung tissues, as well as decreasing their histological alterations and protein content. Total cell number was also reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 56 publications
5
114
0
Order By: Relevance
“…A mouse model study showed that PM2.5 can suppress bronchial epithelial cell autophagy by activating the PI3K/Akt/mTOR pathway 57 . Lipopolysaccharide (LPS) can activate the TLR4/PI3K/Akt/mTOR pathway and further leads to neutrophil infiltration and alveolar wall oedema involving in acute lung injury 58 . All the evidence indicates that targeting PI3K/Akt/mTOR pathway can protect lung epithelial cells and reduce fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model study showed that PM2.5 can suppress bronchial epithelial cell autophagy by activating the PI3K/Akt/mTOR pathway 57 . Lipopolysaccharide (LPS) can activate the TLR4/PI3K/Akt/mTOR pathway and further leads to neutrophil infiltration and alveolar wall oedema involving in acute lung injury 58 . All the evidence indicates that targeting PI3K/Akt/mTOR pathway can protect lung epithelial cells and reduce fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of PI3K/Akt signaling pathway protects tissues or cells against LPS- and CLP-induced-acute lung injury through inhibiting cell apoptosis [ 31 , 32 ]. To further investigate whether DEX protects against LPS-induced lung injury through the PI3K/Akt/FoxO1 signaling pathway, we pretreated the samples with the PI3K/Akt inhibitor LY294002 and BEZ235 before the induction of LPS-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mice were orally treated with three doses of SS (125, 250, and 500 mg/kg) once daily for six consecutive days for preventing paracetamol-induced hepatotoxicity. The dosages of SS were established according to our lab's previous paper [19,20,22]. The administration of various doses of SS did not affect the viability of murine macrophages, while the administration of a nontoxic dose of SS could significantly reduce the levels of LPS-induced NO and proinflammatory cytokines in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional usage, SS has been applied for the treatment of diarrhea, night sweats, hemorrhoids, eczema, stomach pain, bleeding, vaginal discharge, and amenorrhea. The pharmacological effects of SS are reported to include antioxidant, anti-inflammatory, anti-tumor, anti-aging, anti-diabetic, and antiviral effects [21][22][23]. The scientific name "S. sanghuang" was controversial before 2018; data then showed that Phellinus linteus or Inonotus Sanghuang was not the correct name and that it should be S. sanghuang, because a new species that only grew on live mulberry trees had been discovered.…”
Section: Introductionmentioning
confidence: 99%